Studi Kosmologi Stephen Hawking dan Implikasinya terhadap Ateisme - Febriyanti, Salwaa; Bahri, Media Zainul (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
The creation of the universe is an active area of research in modern cosmological science. Discussions about the creation of the universe are endlessly debated. The rapid development of science has led to the belief that many of the world's problems can be solved and answered by science, consequently reducing the active role of religion in everyday life. In reality, the encounter between science and religion generates a range of views, from conflict to integration. This research aims to deeply examine the views of an atheism figure, Stephen Hawking, who rejects the existence of God. This study is conducted from a psychological perspective and personal life, with a primary emphasis on scientific views related to cosmological studies. This research is a library study, using a qualitative methodological approach and the disciplinary approaches of scientific, theological, and philosophical studies. The primary data sources used are the books authored by Stephen Hawking.